Elongation behaviour of filled semi-crystalline polymers in thermoforming - Wittmann, Lisa-Maria; Kurth, Katharina; Drummer, Dietmar (Advances in Materials and Processing Technologies, 2020)
Thermoforming, besides injection moulding and extrusion, belongs to the most important processes of polymer processing. Thin sheets are formed to parts in a so-called stretch-forming process. The properties of the finally formed parts depend on the sheet properties. Amorphous polymers such as polystyrene and polymethylmethacrylate are examples for most popular polymers used in thermoforming because of their wide temperature ranges suitable for processing with thermoforming. Crystalline polymers or reinforced amorphous polymers have a smaller forming window compared to these amorphous polymers but offer several other advantages. For the processing of most crystalline polymers, modifications of the thermoforming process as well as the materials themselves are necessary. This study analyses the influence of fillers on the elongation behaviour of polyeythlene. Furthermore, the interaction between fillers and cross-linking is investigated in thermoforming experiments as well as microscopical analysis. The general aim is to expand the process related knowledge on material behaviour to qualify more semi-crystalline materials for processing in technical thermoforming applications. In this study, the enormous benefit of radiation crosslinking on the elongation behaviour during thermoforming of filled systems could be presented. Subsequent crosslinking of the filled systems enable the thermoforming of filled films, which could not be processed without irradiation.
CRIS-Team Scopus Importer:2023-03-29
Keywords: cross-linking; fillers; glass spheres; semi-crystalline polymers; Thermoforming